2012
DOI: 10.1103/physrevb.86.020507
|View full text |Cite
|
Sign up to set email alerts
|

Competing many-body instabilities and unconventional superconductivity in graphene

Abstract: The band structure of graphene exhibits van Hove singularities (VHS) at doping x = ±1/8 away from the Dirac point. Near the VHS, interactions effects, enhanced due to the large density of states, can give rise to various many-body phases at experimentally accessible temperatures. We study the competition between different many-body instabilities in graphene using functional renormalization group (FRG). We predict a rich phase diagram, which, depending on long range hopping as well as screening strength and abs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
312
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(329 citation statements)
references
References 36 publications
17
312
0
Order By: Relevance
“…The same result has been obtained in fRG approach [122]. Observe that α SC > 1/2, i.e., the divergence of the SC three legged vertex does indeed lads to a SC instability (which, we recall, leads to a d + id or d − id state, each breaks time-reversal symmetry).…”
Section: Patch Modelssupporting
confidence: 79%
See 2 more Smart Citations
“…The same result has been obtained in fRG approach [122]. Observe that α SC > 1/2, i.e., the divergence of the SC three legged vertex does indeed lads to a SC instability (which, we recall, leads to a d + id or d − id state, each breaks time-reversal symmetry).…”
Section: Patch Modelssupporting
confidence: 79%
“…A number of candidate ordered states has been considered, including superconductivity, SDW order, nematic order and so on. See [34,114,116,117,118,119,120,121,122]. Because the density of state diverges at the saddle points at Van Hove doping, each state can be can be self-consistently obtained at weak coupling.…”
Section: Superconductivity In Doped Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…They further argued, based on Ginzburg-Landau arguments, that the time-reversal symmetry breaking chiral d between the potential spin-density-wave and chiral d-wave superconducting states [103], and also embedding the special case of graphene into a broader picture for fermions on hexagonal lattices [38]. Kiesel et al [45] very recently analyzed the same situation using N -patch fRG. This approach is more flexible and also allows the study of doping levels away from the van Hove point, as well as a systematically investigation of how changes in the interaction profile affect the result.…”
Section: Graphene Doped To the Van Hove Singularitymentioning
confidence: 99%
“…For the special case of Hubbard model, we have g = g ′ = U δ α,β /N , where U is the on-site Coulomb repulsion,β denotes the opposite spin, and N is the total number of sites. Although renormalization-group (RG) analysis indicated that superconductivity instability is asymptotically dominant [31], the SDW vertex is the largest at intermediate RG scale and becomes dominant by slightly doping away from the Van Hove singularity [32].…”
Section: (A)mentioning
confidence: 99%